Clinicodemographic profile of head neck oncology patients in COVID-19 pandemic: A descriptive study in a tertiary hospital of Eastern Nepal - Thakur, Rishikesh; Thakur, Sanjeev (Asian Journal of Medical Sciences, 2021)
Background: Head neck cancer needs early diagnosis and treatment for better outcome. There is lack of oncological awareness in our scenario and which is further masked by COVID-19 pandemic. Further masked by scarce published data from eastern Nepal. Aims and Objective: Our study aims to fulfil the lacunae and helps in providing head neck oncological clinicodemographic profile that will be useful for oncological awareness and early detection that ultimately will lead proper management leading to good outcome. Materials and Methods: A descriptive cross sectional study performed during the COVID-19 pandemic between 15th March 2020 to 12th February 2021 for the biopsy or cytology proven head neck cancer patients. Demographic profile and clinical parameters were recorded. Statistical analysis was performed using SPSS- 16 software. Analysis of clinical parameters with subsites was done by Pearson Chi Square test. The p value <0.05 was considered significant. Results: Fifty-six head neck cancer patients were enrolled as per inclusion criteria. Median age and median duration of clinical presentation were 59.5 years and 3.5 months respectively. Higher prevalence of disease noticed in male and higher age group (>60 years). Thyroid cancer was most common site (19.1%) followed by oral cancer (14.3%). Most common presentation was swelling (55.4%) followed by non-healing ulcer (14.3%). Male patients and having history of tobacco/alcohol use had more site specific cancer as evaluated by Pearson chi square test by SPSS-16 with p -value of 0.021 and 0.004 respectively. Conclusions: Most common subsite is thyroid followed by oral cavity. Swelling is most common clinical presentation. Advancing age, male sex and history of tobacco/alcohol use were risk factors.